The Fed's central bank swap lines and FIMA repo facility - Mark Choi; Linda S. Goldberg; Robert Irving Lerman; Fabiola Ravazzolo (Federal Reserve Bank of New York, 2021)
Building on the facility design and application experience from the period of the global financial crisis, in March 2020 the Federal Reserve eased the terms on its standing swap lines in collaboration with other central banks, reactivated temporary swap agreements, and then introduced the new Foreign and International Monetary Authorities (FIMA) repo facility. While these facilities share similarities, they are different in their operations, breadth of counterparties and potential span of effects. This article provides key details on these facilities and evidence that the central bank swap lines and FIMA repo facility can reduce strains in global dollar funding markets and U.S. Treasury markets during extreme stress events.
Keywords: F33; F34; G28; 330; swap line; dollar; liquidity; repo; Federal Reserve lending facilities